Classroom-Based Physical Activity Breaks and Children's Attention: Cognitive Engagement Works! - Schmidt, Mirko; Benzing, Valentin; Kamer, Mario (Frontiers in Psychology, 2016)
Classroom-based physical activity breaks are postulated to positively impact children’s attention during their school day. However, empirical evidence for this claim is scarce and the role of cognitive engagement in enhancing children’s attentional performance is unexplored in studies on physical activity breaks. The aim of the present study was therefore to disentangle the separate and/or combined effects of physical exertion and cognitive engagement induced by physical activity breaks on primary school children’s attention. In addition, the role of children’s affective reactions to acute interventions at school was investigated. Using a 2 × 2 between-subjects experimental design, 92 children between the ages of 11 and 12 years (M = 11.77, SD = 0.41) were randomly assigned to one of four experimental conditions: (1) combo group (physical activity with high cognitive demands), (2) cognition group (sedentary with high cognitive demands), (3) physical group (physical activity with low cognitive demands), and (4) control group (sedentary with low cognitive demands). Attention and affect were measured before and immediately after a 10-minute intervention. ANCOVAs revealed that whereas physical exertion had no effect on any measure of children’s attentional performance, cognitive engagement was the crucial factor leading to increased focused attention and enhanced processing speed. Mediational analyses showed that changes in positive affect during the interventions mediated the effect between cognitive engagement and focused attention as well as between cognitive engagement and processing speed. These surprising results are discussed in the light of theories predicting both facilitating and deteriorative effects of positive affect on cognitive performance.